Lacistema ligiae (Lacistemataceae), a new species from Chapada Diamantina, Bahia, Brazil, with notes on micromorphology - Marinho, Lucas Cardoso; Pimenta, Karena Mendes; Oliveira, Débora Cavalcante De; Alves, Rodolfo De França; Amorim, André Márcio (Phytotaxa, 2021)
The Flora Neotropica treatment of Flaucourtiaceae s.l., by Sleumer, was a milestone in the study of the group and, consequently, of the families that were subsequently segregated from Flaucourtiaceae. Of these, Lacistemataceae comprise 16 tree-shrub species that usually occur in humid forests. However, specimens from campos rupestres in Bahia State, Brazil, were not analyzed by Sleumer so some morphological variation remained unnoticed. Here, we describe Lacistema ligiae, a new species from the campos rupestres of Bahia, and include notes on leaf venation and pollen morphology of related species. Lacistema ligiae can be recognized by leaf blades with sinuous secondary veins, which are covered by long and adpressed trichomes abaxially, hairy filament and ovary, and a distinct style not exceeding the height of the stamen.